PATENT OR NOT TO PATENT NOVARTIS CASE STUDY IN INDIA - Chinmaya Kumar Mohapatra (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In a limited area, the exclusive right given to the author for invention is classified as a patent for a set period of time. Glivec (imatini mesylate), founded by Novartis pharmaceutical company, is recommended for the chronic myeloid leukemia, one of the most common blood cancers in Eastern countries. On 1 April 2013, the Indian Supreme Court released its final judgment rejecting the appeal of the Swiss giant drug maker after more than ample legal infringement concerning their patentability.For the first time in 2006, this same Indian Patent Office rejected Glivec ’s patent under Section 3(d) of the Indian Patent Act, saying it was merely a twistable copy of an existing drug, Imatinib. Novartis has responded to the Indian government by lodging legal challenges, but the final verdict ends the battle in April 2013. Indeed, although the bioavailability of the drug has grown, the High Court has argued that it has not shown improving efficiency and Glivec is not patentable